Business Model and Institutional Evolution of European Football - Rodrigo Mendes Ribeiro Marioni; Hélder Queiroz Pinto Junior (Universidade Salgado de Oliveira, 2020)
The great challenge of this work is to debate the financial and sports transformations that have occurred in the last few years in football and have provided its modernization and economic development. For that, the concepts of business models and their existing approaches in the literature was discussed. Thus, the main foundation of this work was present in the analysis of the business models used by football teams, allowing the investigation of the importance of this concept for the financial sustainability of the teams. From the analysis of the main European clubs, it becomes evident the importance of financial balance and the development of sports management in the current football scene. However, the increase in the financial disparity between the teams, and consequently the loss of competitiveness and unpredictability, put the sport's perpetuity at risk.